Effects of Long-Term FK 506 Therapy on the Alveolar Bone and Cementum of Rats - Nassar, C. A.; Nassar, P. O.; Andia, D. C.; Guimarães, M. R.; Spolidório, Luis Carlos [UNESP] (Elsevier, 2009)
Cyclosporine (CsA) and tacrolimus (FK 506) exert complex, incompletely understood actions on bone. The objective of the study was to evaluate the effects of long-term tacrolimus therapy on the periodontium. Rats were treated for 60, 120, 180, and 240 days with daily subcutaneous injections of 1 mg/kg body weight of FK 506. After the experimental period, we obtained serum levels of calcium and alkaline phosphatase (ALP). After histological processing, the alveolar bone and cementum, as well as volume densities of bone (Vb) and osteoclasts (Vo), were assessed at the regions of the lower first molar. There was a tendency toward a statistically significant decrease in ALP levels with FK 506; however, serum calcium levels increased during the long periods. At 60, 180, and 240 days of treatment with FK 506, we did not observe Vb and Vo alterations. At 120 days of treatment, there was an evident decrease in Vb, but it did not show alveolar bone loss. We did not observe any alterations of cementum among rats treated with FK 506. It may be concluded that FK 506 administration did not induce side effects on the periodontium. © 2009 Elsevier Inc. All rights reserved.
Keywords: alkaline phosphatase; calcium; tacrolimus; alkaline phosphatase blood level; alveolar bone; animal tissue; body weight; bone density; bone mineralization; calcium blood level; cementum; controlled study; drug effect; histology; long term care; male; nonhuman; osteoclast; outcome assessment; priority journal; rat; treatment duration; Animals; Bone and Bones; Bone Cements; Bone Density; Cyclosporine; Immunosuppressive Agents; Male; Mandible; Rats; Tacrolimus